Buscando pistas para prevenir la violencia urbana en Colombia: Conflictos y agresión entre niños (as) y adolescentes de Bogotá. - Enrique Chaux. (Revista de Estudios Sociales, 2002)
Although most of the violence in Colombia does not have a direct relation with the armed conflict, interpersonal violence has received much less attention from the academic community than political violence. This article summarizes a recent study about peer conflicts among children and adolescents who live in difficult socio- Bogotá. During interviews, 56 students (ages8.0 -14.0), 128 stories of recent conflicts ith friends and acquaintances were collected and analyzed. Results indicate that the level of aggression, and physical aggression in particular, was much higher than what has been found in similar studies conducted in developed countries. Although many participants could think of peaceful and constructive alternatives to deal with their conflicts, almost none of them used them in real-life situations. The role played by third parties, the strong emotions felt during the conflicts, the lack of training and practice, and social-desirability issues are proposed as possible explanations for this distance between thoughts and actions related to conflicts. Different implications of the results of the study for assessing peaceful coexistence, and for the development of effective interventions for the prevention of violence by means of education are discussed.